2020
DOI: 10.1016/s2214-109x(19)30525-x
|View full text |Cite
|
Sign up to set email alerts
|

Cooking fuels and risk of all-cause and cardiopulmonary mortality in urban China: a prospective cohort study

Abstract: Background Cooking practice has transitioned from use of solid fuels to use of clean fuels, with addition of better ventilation facilities. However, the change in mortality risk associated with such a transition remains unclear.Methods The China Kadoorie Biobank (CKB) Study enrolled participants (aged 30-79 years) from ten areas across China; we chose to study participants from five urban areas where transition from use of solid fuels to clean fuels for cooking was prevalent. Participants who reported regular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(53 citation statements)
references
References 32 publications
0
52
1
Order By: Relevance
“…A similar result was found in a study in Shanghai Putuo, which found using solid fuel increases the risk of hypertension, CHD, and diabetes 15 ; and a study in Shanxi, China reported an increased risk of hypertension, CHD, stroke, diabetes, and dyslipidemia 16 . A recent study by Yu et al 17 also linked solid fuel use to cardiovascular mortality.…”
Section: Introductionmentioning
confidence: 99%
“…A similar result was found in a study in Shanghai Putuo, which found using solid fuel increases the risk of hypertension, CHD, and diabetes 15 ; and a study in Shanxi, China reported an increased risk of hypertension, CHD, stroke, diabetes, and dyslipidemia 16 . A recent study by Yu et al 17 also linked solid fuel use to cardiovascular mortality.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there are potentially less appreciated or less easily quantifiable risk and protective factors, such as (a) the family environment (now-studied through Family-Wide Association Studies [ 147 ]); (b) the accumulation of physical and emotional stress along the human lifespan [ 148 ]; (c) living in urban versus rural environments, and in slum versus non-slum urban environments [ 149 151 ]; and (d) specific nutritional habits, such as milk and milk product consumption [ 152 ]. These factors may be worth exploring in the future, regarding their association with specific and integrated neurological conditions, thus combining epidemiological and environmental neuroscience [ 153 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, economically underdeveloped areas tend to face problems of both low utilization of non-clean energy and poor or absent ventilation ( 54 ), increasing the local disease burden of lung cancer. Improving ventilation is also proven to be effective in the houses using clean energy since indoor air pollution is unavoidable ( 57 , 58 ). Also, Chinese-style cooking is a noteworthy risk factor for lung cancer because it often involves more volatilization of heated non-refined oil and exposure to more fumes ( 53 , 59 ).…”
Section: Main Risk Factors Of Lung Cancer and Distributions In Chinamentioning
confidence: 99%
“…Second, it has been reported that a significant reduction occurred in mortality from cardiopulmonary diseases after withdrawing solid fuels ( 57 ). Although the utilization rate of clean energy in China has been increasing from 43% to 64% between 2000 and 2018 ( 79 ), there is still a big gap between China and the United States, Europe, and other developed countries (with a proportion over 95%), indicating that promoting the use of clean energy (e.g., electricity and natural gas) can effectively alleviate the burden of lung cancer disease in China, which is of great urgency.…”
Section: Prevention Strategies For Lung Cancermentioning
confidence: 99%